2019
DOI: 10.7589/2017-12-295
|View full text |Cite
|
Sign up to set email alerts
|

Fibropapillomatosis in a Green Sea Turtle (Chelonia mydas) from the Southeastern Pacific

Abstract: Fibropapillomatosis is a neoplastic disease that afflicts sea turtles. Although it is disseminated worldwide, cases of the disease have not been reported in the southeastern Pacific region. We describe a case of fibropapillomatosis in a green sea turtle ( Chelonia mydas) during its rehabilitation at the Machalilla National Park Rehabilitation Center, Ecuador. Viral presence was confirmed by PCR, targeting fragments of the chelonid alphaherpesvirus 5 (ChHV5) unique long (UL) genes, UL27, UL28, and UL30. The amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…Samples collected from turtles from a particular region tend to cluster into the associated phylogeographic group. For example, samples from Brazil cluster into the Atlantic [23] and samples from Ecuador into Pacific [25]. Variation in ChHV5 has also been described at more local levels, with four variants in Florida [26] and six variants in Brazil [23].…”
Section: Introductionmentioning
confidence: 99%
“…Samples collected from turtles from a particular region tend to cluster into the associated phylogeographic group. For example, samples from Brazil cluster into the Atlantic [23] and samples from Ecuador into Pacific [25]. Variation in ChHV5 has also been described at more local levels, with four variants in Florida [26] and six variants in Brazil [23].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors may contribute to the expression and the severity of the disease [ 82 , 85 , 86 ]. The disease was first reported in an aquarium in New York [ 87 ], but is now reported globally in tropical waters [ 51 , 84 , 88 – 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some of the more detailed descriptions are from sea turtles, tortoises and crocodiles. Grey patch disease and FP, characterised by coalescing greyish papular skin lesions (spreading patches) and branching papillary tumours ( Figure 6 ), respectively, have been reported in sea turtles ( 42 , 54 , 108 , 109 ). Lung-eye-trachea disease (LETD) with a clinical course of 2–3 weeks has been seen in green sea turtles ( 98 ).…”
Section: Clinical and Pathological Signsmentioning
confidence: 89%
“…FP is a debilitating disease characterised by the development of tumours ( 119 , 120 ). Depending on the location of the tumours, FP can have detrimental effects ( 109 , 121 ). On the basis of prevalence and distribution, Tagliolatto et al reported a prevalence rate of 43% for FP in green turtles captured in a foraging area in south-eastern Brazil ( 121 ).…”
Section: Epidemiologymentioning
confidence: 99%